A historical study of the Philippine Collegian and how much press freedom it enjoyed based on content analyses and random interviews of editors 1922-2002 - Castel, Ellen Joy Ubarra (Quezon City College of Mass Communication, University of the Philippines Diliman, 2006)
"The Philippine Collegian, as a campus newspaper, ideally seeks to "maintain a strong, unfettered voice [and] thrive on thorny issues" (Crimmins, 1968) of campus as well as national concern. It exists to serve the best interest of the university students. From its initial publication in 1922 to the present, the Philippine Collegian has established an unsullied reputation for liberalism. Although the Philippine Collegian as a subject of research has always been chosen by many, there still hasn't been any historical study of the publication that covered a comprehensive time period. That is, encompassing its first years up until recent time. There also hasn't been any study that focused on analyzing its development in the context of how much press freedom it enjoys. Foremost in this study is to gauge the state and exercise of freedom of the press in the publication throughout the different stages of its history in its eighty years of existence from 1922. The researchers made use of qualitative methods such as bibliographical research and focus interviews with former editors of the Philippine Collegian from 1960-2002. Also, the researchers used content analysis of selected editorial articles during the same period, to confirm if the actual contents of paper verify the claim of the interviewees. In this study, the press freedom enjoyed by the Philippine Collegian was assessed through the following aspects: freedom from prior restraint (campus journalism rules and regulations implemented by the university president and Board of Regents, intervention both by the university administration and the government, the presence of a faculty adviser from 1922-1977 and the extent of his/her power; the existence of taboo subjects if there were any); freedom from subsequent punishment (incidences of expulsion, suspension, intimidation, or punishment of staff members due to their published articles); freedom of circulation (funding and other factors that affect circulation); and freedom of access to information (accessibility of information regarding issues that were tackled). The study assumed that as long as any of these aspects are manifested in the management and publication of the Philippine Collegian, the paper enjoyed a degree of press freedom. Thus, in order to provide a more precise description of Press Freedom in the paper, the researchers made use of the ff. categorizations: free, relatively free, partially free, repressed and no freedom at all. This study reveals that based on the manifestations of the four aspects of press freedom, the Philippine Collegian was only partially free during the 1920's-1950's, relatively free during the 1960's, most repressed during the 1970's to early 1980's, and freest after the lifting of martial law. Also, the study showed that the degree of press freedom that the Philippine Collegian enjoyed over time was a product og various factors. These were: the UP community that nurtured it with liberalism: the studentry that demanded critical thought and responsible journalism from the paper, the staffers which fought for their right to free expression and at the same time tested the limits of press freedom; and the social and political events in the country that shaped the paper's character and called for its activism and involvement."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman